Plant cell wall lignification and monolignol metabolism - Wang, Yin; Chantreau, Maxime; Sibout, Richard; Hawkins, Simon (Frontiers in Plant Science, 2013)
Plants are built of various specialized cell types that differ in their cell wall composition and structure. The cell walls of certain tissues (xylem, sclerenchyma) are characterized by the presence of the heterogenous polymer lignin that plays an essential role in their physiology. This phenolic polymer is composed of different monomeric subunits - the monolignols - that are linked together by several covalent bonds. Numerous studies have shown that monolignol biosynthesis and polymerization to form lignin are tightly controlled in different cell types and tissues. However our understanding of the genetic control of monolignol transport and polymerization remains incomplete, despite some recent promising results. This situation is made more complex since we know that monolignols or related compounds are sometimes produced in non-lignified tissues. In this review, we focus on some key steps of monolignol metabolism including polymerization, transport and compartmentation. As well as being of fundamental interest, the quantity of lignin and its nature are also known to have a negative